2015
DOI: 10.3390/agriculture5030723
|View full text |Cite
|
Sign up to set email alerts
|

Fourfold Increase in Pumpkin Yield in Response to Low-Dosage Root Zone Application of Urine-Enhanced Biochar to a Fertile Tropical Soil

Abstract: A widely abundant and invasive forest shrub, Eupatorium adenophorum, was pyrolyzed in a cost-efficient flame curtain kiln to produce biochar. The resulting biochar fulfilled all the requirements for premium quality, according to the European Biochar Certificate. The biochar was either applied alone or mixed with fresh cow urine (1:1 volume) to test its capacity to serve as slow release fertilizer in a pumpkin field trial in Nepal. Treatments included cow-manure compost combined with (i) urine-only; (ii) biocha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 76 publications
11
117
1
3
Order By: Relevance
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
“…This is probably due to the positive interaction between BC and applied fertiliser that improved the availability of nutrients associated with enhanced plant uptake and reduced losses of these nutrients. Schmidt et al (2015) reported an 85% increase in pumpkin crop yield versus the control following soil application of Eupatorium weed-derived BC. The yield rose to 300% when cattle urine was added to this BC before soil application.…”
Section: Interaction With Organic and Inorganic Fertilisersmentioning
confidence: 99%
“…In 2012, the quantity of plant nutrients used per unit of arable land was 28.4 kg · ha −1 , which is very low even by South Asian standards [2]. Nepal imports all of its chemical fertilizers but the supply is not sufficient to meet the demand.…”
Section: Introductionmentioning
confidence: 99%
“…As with other inputs, the quality of the supply is also a serious issue. Application of poor quality fertilizer results in lower than anticipated impacts on crop productivity and profitability [2,3]. The imported fertilizers are expensive and prices are rising, which further limits access, especially for poor farmers.…”
Section: Introductionmentioning
confidence: 99%
“…loaded with nutrients, activated to change porosity and chemical properties) belong to the more promising soil GHG mitigation amendments Novak et al 2014;Kammann et al 2015;Schmidt et al 2015;Mukherjee et al 2014). Biochar is the solid product that results from pyrolysis of organic materials (Verheijen et al 2010;Sohi et al 2010;Keiluweit et al 2010) having properties that depend on used technology and feedstock (Keiluweit et al 2010;Libra et al 2011;Enders et al 2012).…”
Section: Introductionmentioning
confidence: 99%